Optimizing Konjac Glucomannan Hydrolysate (KGMH) as a Natural Binder in Foam Mat Drying for Functional Herbal Powder Drink - Alwani Hamad; Zahwa Kinanti; Pachara Pomsang; Mubshair Naveed; Dwi Hartanti (Research in Chemical Engineering, 2025)
Phytochemical-rich herbal beverages are typically perishable due to their liquid form. Powder conversion via foam mat drying offers improved shelf stability but requires effective natural binders. Konjac glucomannan (KGM) is a promising candidate, though its high viscosity necessitates enzymatic hydrolysis to produce functional konjac glucomannan hydrolysate (KGMH). This study investigated konjac glucomannan hydrolysate (KGMH) as a natural binder for foam mat drying of a herbal blend (Java tea, turmeric, and seed-under-leaf). The research optimized KGMH functionality by evaluating KGM source (Thailand vs. Indonesia), enzyme concentration (100–200 IU/g), and KGM concentration (10–30% w/v) on KGMH properties (viscosity, reducing sugar, total carbohydrate, and degree of polymerization (DP)), herbal drink powder characteristics (physical, phenolic, and flavonoid content, also antioxidant activity using DPPH and FRAP methods). The herbal powder was produced by mixing the herbal extract with KGMH to form a stable foam, followed by drying at 60°C for 12 hours and grinding into powder. Results demonstrated that Enzymatic hydrolysis significantly reduced KGMH viscosity and DP, while increasing reducing sugars, with Indonesian konjac yielding higher viscosity than Thai konjac, and higher KGM concentrations increasing viscosity but requiring greater enzyme levels for effective depolymerization. The herbal drink using binder from Thai KGMH at 200 IU/g enzyme and 20% KGM concentration produced the highest retention of total phenolic content (2.83 mg GAE/g), total flavonoids (3266.52 mg QE/g), and antioxidant activity (93.53 mM TE/g by FRAP) in the herbal drink powder